Test embankment on sensitive clay / by Charles C. Ladd. - Ladd, Charles C. (Charles Cushing); Massachusetts Institute of Technology. Department of Civil Engineering. (Tufts University. Tisch Library., 2019)
1 online resource (29 leaves) : illustrations.; "Preprint of paper prepared for ASCE Soil Mechanics and Foundations Division Speciality Conference on Performance of Earth and Earth-supported structures, Purdue University, June 1972."; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.